Measuring mortality through a primary health care network (Colombia Medica, 1990)
This study presents the subregistered figure and discrepancy between the causes of death, in total 1985-86 death rate in the Valle del Cauca, Colombia, when comparing the DANE routine systems of collection and analysis of death statistics (316 deaths) with the ones that are recorded when using the (extramural) primary attention network (355 deaths) coordinated through volunteer agents and educational and sanitary officials. Significant statistical differences were found in the subregistered figure depending on age, place of residence, and month of death. A prominent descending curve of the subregistered figure, depending on age, and the disappearance of the subregistered figure after 9 months of observation with the primary network case stands out.The subregistered figure recorded during one year of observation was 10.9%, with discrepancies in the basic causes of death mainly in deaths with a diagnosis related to the cardiovascular system, with an almost total absence in deaths with a diagnosis related to cancer. A 26.6% of discordant causes was observed. The recording capacity of the death rates by the (extramural) primary attention network and the importance of the knowledge of the "day-to-day" death figures in health institutions for the making of decisions in the educational area as well as in the administrative areas for the improvement of health services were observed.